Medial Patellar-femoral Ligament Reconstruction in Recurrent Patella Dislocation. Case Report - Ochoa-Cázares, René; Acosta-González, Marvin Antonio (Revista Colombiana de Ortopedia y Traumatología, 2020)
Introduction: Patellar-femoral instability is a condition where recurrent dislocations and partial dislocations events are present. The medial patellar-femoral ligament (MPFL) is the main responsable to avoid lateral patellar displacement between full extension and 30 degrees of knee flexion. Clinical Case: Male, 20 years old with recurrent patellar dislocations and clinical patellarfemoral instability of right knee. Discussion and conclusion: The main Objective of MPFL recosntruction surgery is to restore medial knee stability against lateral patellar movement, in this case we found that the MPFL reconstruction with an anatomic technique of bone tunnels is a correct alternative to consider in the treatment of recurrent patellar dislocation.